Entwicklung eines mikrofluidischen Zweikammer-Chipsystems mit integrierter Sensorik für die Anwendung in der Tumorforschung - Rajabi, Taleieh (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2014)
We have developed a microfluidic two-layered channel system based on polycarbonate to investigate the transmigration of cancer cells under flow conditions and defined shear rate using live cell microscopy. The two layers are separated by a porous membrane with an endothelial monolayer on top of the membrane to mimic the blood vessel wall. To extend the measuring capabilities of our microfluidic chip, gold electrodes were structured on the membrane using optical lithography and chemical etching.